Effect of dimensionless heat input during laser solid forming of high-strength steel. (10th February 2022) - Huang, Chunping; Liang, Renyu; Liu, Fenggang; Yang, Haiou; Lin, Xin
Highlights: Extensive study of the effect of energy density on high-strength steel by Laser solid forming (LSF). The evaluation method of dimensionless heat input Q * is specially introduced. Under three different heat inputs Q *, microstructures were observed, and the characteristics of their formation were analyzed. The Q * value has an important influence on the mechanical properties of high-strength steel by LSF. Abstract: Laser solid forming (LSF) technology can be used to rapidly manufacture and repair high-strength steel parts with superior performance, but the value of the heat input during operation is difficult to quantify, which has a substantial impact on the microstructure and mechanical properties of the parts. A promising method to improve the forming efficiency and quality of LSFed parts is to accurately control the heat input and explore its relationship with the microstructure and mechanical properties. To remove the interference of other variables from the experiment, the dimensionless heat input Q * was introduced. The Q * values were designed in advance to calculate the experimental parameters used to perform the LSF experiment. The microstructure was observed at different regions of the sample, and its mechanical properties were analyzed. From the results, the following conclusions were drawn. The Q * value was directly related to the cooling rate and heat accumulation in the top structure, leading to the formation of different microstructures; it also modified the original structure at the bottom, affecting the subsequent thermal cycle and indirectly changing the tempered martensite morphology. The heat input also affected the mechanical properties of the sample. The hardness of the stable zone decreased with increasing Q * value, and the lowest value was 190 HV. Similarly, the tensile strength and yield strength of the LSFed samples decreased considerably with increasing Q * value, and the lowest values were 735 and 604 MPa, respectively. Only the elongation and reduction in the area increased after a slight decrease. The Q * value had a significant effect on heat treatment. When Q * = 2.9, the increase in tensile strength and yield strength after heat treatment was the largest (29% and 44%, respectively). Graphical abstract: Image, graphical abstract